Consolation and medicine in Luther's "Whether One May Flee from a Deadly Plague". Issue 2 (16th June 2022) - Schiefelbein‐Guerrero, Kyle
Abstract: This article analyzes Luther's 1529 letter "Whether One May Flee from a Deadly Plague" through the lenses of Reformation consolation literature and the prevailing medical theories at the time to highlight Luther's concerns about sickness, holding together theological and practical medical advice. Luther's letter addresses key theological concerns about God and neighbor that are central to today's engagement with the world, including his Christology, his relational view of the person, the vocation of care, and the two‐kingdoms way of describing how God operates.